Developing a theory-driven contextually relevant mHealth intervention. Issue 1 (1st January 2019) - Jennings, Hannah Maria; Morrison, Joanna; Akter, Kohenour; Kuddus, Abdul; Ahmed, Naveed; Kumer Shaha, Sanjit; Nahar, Tasmin; Haghparast-Bidgoli, Hassan; Khan, AK Azad; Azad, Kishwar; Fottrell, Edward
ABSTRACT: Background : mHealth interventions have huge potential to reach large numbers of people in resource poor settings but have been criticised for lacking theory-driven design and rigorous evaluation. This paper shares the process we developed when developing an awareness raising and behaviour change focused mHealth intervention, through applying behavioural theory to in-depth qualitative research. It addresses an important gap in research regarding the use of theory and formative research to develop an mHealth intervention. Objectives : To develop a theory-driven contextually relevant mHealth intervention aimed at preventing and managing diabetes among the general population in rural Bangladesh. Methods : In-depth formative qualitative research (interviews and focus group discussions) were conducted in rural Faridpur. The data were analysed thematically and enablers and barriers to behaviour change related to lifestyle and the prevention of and management of diabetes were identified. In addition to the COM-B (Capability, Opportunity, Motivation-Behaviour) model of behaviour change we selected the Transtheoretical Domains Framework (TDF) to be applied to the formative research in order to guide the development of the intervention. Results : A six step-process was developed to outline the content of voice messages drawing on in-depth qualitative research and COM-B and TDF models. A table to inform voice messages was developed and acted as a guide to scriptwriters in the production of the messages. Conclusions : In order to respond to the local needs of a community in Bangladesh, a process of formative research, drawing on behavioural theory helped in the development of awareness-raising and behaviour change mHealth messages through helping us to conceptualise and understand behaviour (for example by categorising behaviour into specific domains) and subsequently identify specific behavioural strategies to target the behaviour.